DESIGN OF ASYMMTERIC HALF -BRIDGE CONTROL CIRCUIT FOR 8/6 SWITCHED RELUCTANCE MOTOR - Yesayevtta, Denri
Electric motors have become a trend in the development of the motor world, displacing the role of combustion engines. Electric motors themselves are divided into several types, and one of the electric motors that is targeted for future use is the Switched Reluctance Motor (SRM). SRM is assumed to replace BLDC motors and induction motors. SRM is a synchronous motor that requires a converter to control its operation. This control consists of several parts such as position control, voltage control, and the converter circuit itself, which is used to regulate the phase operation sequence of the motor. The converter consists of various topologies, including AHB (Asymmetric Half-Bridge), shared switch, R-dump, and Miller. Through a weighted comparison of several aspects, AHB is selected as the preferred topology with the highest value. AHB has the highest robustness due to its ability to operate independently among its phases. Simulation results using Matlab Simulink software also demonstrate the operation of AHB in controlling the phases of the SRM alternately. Through the conducted testing, the test circuit consists of the input voltage source to the converter circuit and the voltage towards the MOSFET control circuit. The TI C2000 device is used in the testing as a signal generator for MOSFET control. The test results show that the motor's performance aligns with the simulation and the theoretical foundation.